Analisis Awal Gerak Butiran Pada Transport Sedimen Material Gambut - Yearni Yudika Friniati Putri; Sigit Sutikno; Muhammad Yusa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
In addition to peatland fires and the conversion of peatland into plantations, a serious problem is the abrasion of peaty beaches. Abrasion is the result of sediment transport processes parallel to the shoreline(longshore sediment transport). Basically, the study of sediment transport begins by identifying the interacting properties of sediment and flow. The interaction in question is a condition where the flow beginsto cause the movement of the particles it passes through until a displacement occurs. The purpose of this research is to analyze the parameters resulting from theoretical calculations for peat material based on Shield theory. This research is a physical modeling without scale of the movement of particles in a channel.The initial process of sediment movement is simulated in a flume in the laboratory which has been given samples of peat sediment and sand sediment (as a comparison) at the bottom. Both samples are uniformgrains with 0.25 – 4.75 mm diameter. After the simulation is done, the results of the observation are compared with theoretical calculations. Based on calculations using the Shields theory, the shear stressvalues for peat sediments ranged from 0.124 – 1.523 N/m2 and shear velocity ranged from 0.011 – 0.039 m/s.Key words: Peat, Initiation motion, Shields Theory, Critical Shear Stress